Al-Imam Ibnu Hazm Wa Juhuduhu Al-'Ilmiyyah - H. Lalu Muhamad Fazlurrahman (UIN Mataram, 2020)
One of the imams who had a lot of role and impact in the growth of islamic sciences is Imam Ibn Hazm, his name is not as famous as Imam Al-Syafi’i as the main reference for indonesian moslems the majority of them are followers of the Syafi’i madhhab, Ibn Hazm’s thoughts are like the madhhab adopted by him the Azzohiriyah School looks simple, literally and textual but if it is studied in more depth and more detail it turns out to have strong scientific arguments. Therefore studying his thoughts and the methode of Imam Ibn Hazm in concluding the conclusions of laws are very important in responding to various contemporary problems which are increasingly complex, with that motivation the researcher tries to present a scientific article about Imam Ibn Hazm his personal life, and his methods of his ijtihad which generally refuse analogy (qiyas) and consistently adhere to the texts of the al-qur’an and hadith and ijma’ or the consensus of the moslems. His thoughts and methods are seen to be different from the majority of other scholars who continue to make qiyas or analogies as a source of islamic law, but precisely for that reason the study of Ibn Hazm and his thoughts becomes interesting and important to do. Keywords : Imam Ibn Hazm, the source of islamic law, textual.